Biomonitoring of the Genotoxic and Hepatotoxic Effects and Oxidative Stress Potentials of Itraconazole in Pregnant Rats. (27th April 2015) - El‐Shershaby, Abdel‐Fattah; Dakrory, Ahmed I.; El‐Dakdoky, Mai H.; Ibrahim, Jehane; Kassem, Fatma
<x xml:space="preserve">Abstract</x> BACKGROUND Pregnant women are more susceptible to both vaginal colonization and infection by yeast. One hundred million fungal infected patients have been treated worldwide with itraconazole (Caputo, 2003. METHOD Itraconazole was administrated orally to pregnant rats at doses of 75, 100, or 150 mg/kg during gestational days (GD) 1 to 7 or GD 8 to 14 or GD 14 to 20. The genotoxicity and hepatotoxicity of the antifungal drug itraconazole were assessed during different periods of pregnancy using different methods. RESULTS It was found that itraconazole was a genotoxic drug for both mothers and fetuses. This finding was observed via significant elevation in the estimated comet assay parameters (percentage of fragmented DNA, tail moment, and olive moment), percentage of fragmented DNA measured by diphenylamine assay and mixed smearing and laddering of DNA fragments of liver samples. In addition, itraconazole caused significant elevation in the level of hepatic malondialdehyde and depletion in the catalase activity and glutathione level. Furthermore, itraconazole induced histopathological alterations in the hepatic tissues of both mothers and fetuses. CONCLUSION These findings indicate that itraconazole administration at doses of 75, 100, or 150 mg/kg during pregnancy induced maternal and fetal toxicity that could be induced by the genotoxicity and the oxidative damage